Kajian Literatur: Pengaruh E-Modul Interaktif Terhadap Motivasi Siswa dalam Pembelajaran - Rahmawati, Lia; Bachri, Bachtiar Syaiful; Maureen, Irena Yolanita (Paedagogie, 2025)
Along with advancements in educational technology, interactive e-modules have emerged as a promising innovation expected to enhance the quality of learning across various educational levels. This article aims to review existing literature on the impact of interactive e-module usage on student motivation and engagement in learning. A systematic literature review method was employed, involving a comprehensive search of scholarly articles published between 2022 and 2024. The databases used included Google Scholar, ERIC (Education Resources Information Center), Science Direct, and the Garuda portal. Data were analyzed using a thematic analysis approach. The findings indicate that the use of interactive e-modules positively influences student motivation, particularly in terms of active participation and learning desire. These e-modules foster greater student involvement in the learning process and contribute to making learning more engaging and effective. Several factors affect the effectiveness of e-modules, including appealing module design, interactivity, and accessibility of technology. Overall, interactive e-modules hold substantial potential to improve learning quality by enhancing student motivation.